How do you convert 2y=3y^2-4x^2 -2x 2y=3y24x22x into a polar equation?

1 Answer
Mar 27, 2017

r=(2(sintheta+costheta))/(3sin^2theta-4cos^2theta)r=2(sinθ+cosθ)3sin2θ4cos2θ

Explanation:

The relation between polar coordinates (r,theta)(r,θ) and Cartesian coordinates (x,y)(x,y) is given by x=rcosthetax=rcosθ and y=rsinthetay=rsinθ

Hence, 2y=3y^2-4x^2-2x2y=3y24x22x

hArr2rsintheta=3r^2sin^2theta-4r^2cos^2theta-2rcostheta2rsinθ=3r2sin2θ4r2cos2θ2rcosθ

i.e. r^2(3sin^2theta-4cos^2theta)=2r(sintheta+costheta)r2(3sin2θ4cos2θ)=2r(sinθ+cosθ)

or r=(2(sintheta+costheta))/(3sin^2theta-4cos^2theta)r=2(sinθ+cosθ)3sin2θ4cos2θ